American Journal of Sociology. (JSTOR.)
Established in 1895 as the first US scholarly journal in its field, the American Journal of Sociology (AJS) presents pathbreaking work from all areas of sociology, with an emphasis on theory building and innovative methods. AJS strives to speak to the general sociology reader and is open to contributions from across the social sciences$1 (Bpolitical science, economics, history, anthropology, and statistics in addition to sociology$1 (Bthat seriously engage the sociological literature to forge new ways of understanding the social. AJS offers a substantial book review section that identifies the most salient work of both emerging and enduring scholars of social science. Commissioned review essays appear occasionally, offering the readers a comparative, in-depth examination of prominent titles.s
Keywords: Social Sciences